2016
DOI: 10.2174/1874471009666161028150654
|View full text |Cite
|
Sign up to set email alerts
|

Gallium-68 in Medical Imaging

Abstract: Over the past several years, Positron Emission Tomography (PET) imaging agents labeled with ;68Gallium (68Ga) have undergone a significant increase in clinical utilization. 68Ga is conveniently produced from a germanium-68/gallium-68 (68Ge/68Ga) generator. Because of the compact size and ease of use of the generator, 68Ga labeled compounds may be more cost-effective than PET radioisotopes that are cyclotron-produced. The convenient half-life of 68Ga (T1/2=68 min) provides sufficient radioactivity for various P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 0 publications
2
46
0
Order By: Relevance
“…Variation of pH of the reaction mixture revealed that the maximum radiochemical yield could be obtained when the pH of the reaction mixture was maintained between 4 and 5. This is in agreement with the reported value of pH required for labeling of DOTA or its derivatives with 68 Ga (Bhadwal et al, ; Burke et al, ; Kilian, ; Martiniova et al, ). The effect of incubation time and temperature on the complexation yield revealed that approximately 20 min of incubation in a boiling water bath is required to prepare the agent with near quantitative yield.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Variation of pH of the reaction mixture revealed that the maximum radiochemical yield could be obtained when the pH of the reaction mixture was maintained between 4 and 5. This is in agreement with the reported value of pH required for labeling of DOTA or its derivatives with 68 Ga (Bhadwal et al, ; Burke et al, ; Kilian, ; Martiniova et al, ). The effect of incubation time and temperature on the complexation yield revealed that approximately 20 min of incubation in a boiling water bath is required to prepare the agent with near quantitative yield.…”
Section: Resultssupporting
confidence: 91%
“…As direct incorporation of 68 Ga in gemcitabine moiety (Figure A) is difficult, radiolabeling was attempted through a bi‐functional chelating agent (BFCA). DOTA (1,4,7,10‐tetraazacyclododecane‐1,4,7,10‐tetraacetic acid) can be used as a suitable BFCA for developing 68 Ga‐based agents for radiodiagnostic applications (Burke, Clemente, & Archibald, ; Kilian, ; Martiniova, De Palatis, Etchebehere, & Ravizzini, ). Therefore, for the present study p ‐NCS‐benzyl‐DOTA [2,2′,2″‐(10‐(1‐carboxy‐4‐((4‐isothiocyanatobenzyl) amino)‐4‐oxobutyl)‐1,4,7,10‐tetraazacyclododecane‐1,4,7‐triyl)‐triacetic acid] was chosen as the BFCA to couple with gemcitabine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Favorable coordination chemistry that eases coupling to small biomolecules and gallium's affinity towards tumor tissue (it has been used as chemotherapy agent) impulse 68 Ga as a potential alternative to 18 F-and 11 C-PET radiopharmaceuticals. Many 68 Ga complexes have been applied in nuclear medicine [22,35]. 68 Ga-EDTA was used to study blood-brain barrier integrity and renal function [36,37].…”
Section: Small Molecule Clinical Applications Of 68 Gamentioning
confidence: 99%
“…Gallium‐68 ( 68 Ga) has attracted a great amount of interest due to its several important advantages. The half‐life of 68 Ga (t 1/2 = 68 min) is short and suitable for PET radiochemistry, and it decays by up to 89% through the positron emission of a maximum of 1.92 MeV of energy, without requiring any additional gamma contribution . 68 Ga can be easily obtained from a 68 Ge/ 68 Ga generator, and several of such systems are commercially available.…”
Section: Introductionmentioning
confidence: 99%